Faktor – Faktor Yang Mempengaruhi Ibu Nifas Terhadap Kepatuhan Dalam Mengkonsumsi Tablet Fe Di Wilayah Puskesmas Ketapang 1 Sampit Kalimantan Tengah - Yati, Eka Veramudi; Rahmawati, Dwi; Melviani, Melviani (Akademi Kebidanan Bunga Husada Samarinda, 2023)
Background: Administration of FE tablets as a supplement is an effort to increase iron (FE) levels in a short period of time, this is done to prevent FE deficiency in postpartum women caused by a lack of iron absorbed by the body through foods containing iron. Objective: To find out the factors that influence postpartum women's compliance in consuming FE tablets at the Ketapang 1 Sampit Health Center, Central Kalimantan. Methods: This study used an analytic survey method with a cross sectional approach. The number of samples in this study were 30 people. The sampling technique in this study used purposive sampling with the criteria for postpartum women who were in the Ketapang 1 Health Center area and were still in the postpartum period. The research instrument used a questionnaire. Results: In the Chi-Squere statistical test, knowledge of compliance was obtained (p equal to 0.001). Family support for compliance (p equal to 0.000). Side effects on adherence (p equal to 0.009). Motivation towards compliance (p equal to 0.015). Conclusion: Knowledge, family support, side effects and motivation affect maternal adherence in consuming FE tablets, therefore it is expected that husbands and families can provide support for postpartum mothers so that postpartum mothers can increase their compliance in consuming FE tablets regularly.